Management of infective endocarditis in pregnancy by a multidisciplinary team: a case series - Shapero, Kayle S.; Nauriyal, Varidhi; Megli, Christina; Berlacher, Kathryn; El-Dalati, Sami (Therapeutic advances in infectious disease, 2022)
Introduction: The incidence of infective endocarditis (IE) in pregnancy is rare and has been increasing during the opioid epidemic. IE in pregnancy is associated with high rates of maternal and fetal morbidity and mortality. Multidisciplinary endocarditis teams for management of IE have been shown to reduce in-hospital and 1-year mortality. We present a single-center experience managing IE in pregnancy utilizing a multidisciplinary endocarditis team. Methods: Patients diagnosed with IE while pregnant or within 30 days post-partum were identified. All patients discussed at the institution’s weekly multidisciplinary endocarditis meeting were included. Demographic and clinical data and outcome-related variables were retrospectively reviewed and recorded. Results: Between 1 October 2020 and 1 June 2021 6 pregnant or 30-day post-partum patients with IE were identified. All patients had co-morbid injection drug use; Staphylococcus aureus was the etiologic pathogen in all patients. All patients had embolic complications and 5 required ICU admission and mechanical ventilatory support. Four patients underwent valve replacement. There were no patient-directed discharges. All patients survived to hospital discharge and 90-days after diagnosis. Four pregnancies resulted in delivery at an average gestational age of 32.4 weeks with 3 requiring NICU admissions and prolonged lengths of stay. All patients were seen by addiction medicine and 5 were started on medication-assisted treatment for opioid use disorder. Discussion: In a small retrospective cases series, coordination of care by a multidisciplinary endocarditis team led to a high-rate of surgical intervention with no patient-directed discharges and no in-hospital or 90-day mortality. Conclusion: Multidisciplinary endocarditis teams are a low-risk intervention that may improve outcomes in pregnant patients with IE.